2012
DOI: 10.1161/atvbaha.112.255208
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-Activated Receptor δ Inhibits Human Macrophage Foam Cell Formation and the Inflammatory Response Induced by Very Low-Density Lipoprotein

Abstract: Objective-Hypertriglyceridemia is an important risk factor for cardiovascular disease. Elevated plasma very low-density lipoprotein (VLDL) puts insulin-resistant patients at risk for atherosclerosis. VLDL readily induces macrophage lipid accumulation and inflammatory responses, for which targeted therapeutic strategies remain elusive. We examined the ability of VLDL to induce macrophage foam cells and the inflammatory response and sought to define the cell signaling cascades involved. We further examined the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…Moreover, Kupffer cell-specifi c deletion of Ppard in mice resulted in increased proinfl ammatory cytokine expression and reduced anti-infl ammatory cytokine expression, which was coupled to increased liver TG accumulation and hepatic dysfunction ( 54 ). Therefore, our results are consistent with an anti-infl ammatory role for PPAR ␦ activation in the liver, similar to the effect in macrophages and in the aorta ( 28,45,47 ). The relative impact of reduced infl ammation versus correction of insulin sensitivity to the attenuation of hepatic steatosis cannot be discerned from the present experiments and requires further elucidation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, Kupffer cell-specifi c deletion of Ppard in mice resulted in increased proinfl ammatory cytokine expression and reduced anti-infl ammatory cytokine expression, which was coupled to increased liver TG accumulation and hepatic dysfunction ( 54 ). Therefore, our results are consistent with an anti-infl ammatory role for PPAR ␦ activation in the liver, similar to the effect in macrophages and in the aorta ( 28,45,47 ). The relative impact of reduced infl ammation versus correction of insulin sensitivity to the attenuation of hepatic steatosis cannot be discerned from the present experiments and requires further elucidation.…”
Section: Discussionsupporting
confidence: 80%
“…6C ). A similar response of these two cytokines to GW1516 was reported in cultured macrophages ( 47 ), suggesting that a direct effect of GW1516 on the expression of Ccl3 and Il1b contributed to their decreased expression in liver following GW intervention ( Fig. 6A ).…”
Section: Gw1516 Inhibits Hepatic Infl Ammation and Induction Of Endopsupporting
confidence: 76%
“…anti-inflammatory role of PPARδ in CS-related airway inflammation. It has been found that treatment with a synthetic PPARδ agonist inhibited activation of p38 MAP kinases in inflammatory circumstance, 19,28,32 which suggested a tight link between PPARδ and p38 MAPK. The MAPK family includes three members: p38, ERK and c-Jun N-terminal kinase (JNK).…”
Section: Discussionmentioning
confidence: 99%
“…18 Evidences concerning the impact of PPARδ in inflammatory process have increased in the last few years. PPARδ activation effectively inhibited very low-density lipoprotein-induced IL-1β release in THP-1 macrophages, 19 lipopolysaccharideinduced TNFα production in cardiomyocytes, 20 and TNFα-induced expression of vascular cell adhesion molecule-1 in human umbilical vein endothelial cells. 21 However, the potential roles of PPARδ in inflammatory responses of lung remain unknown.…”
mentioning
confidence: 98%
“…signaling [32]. The anti-inflammatory effects of PPARD agonists in macrophages have been shown by several groups.…”
Section: Macrophagesmentioning
confidence: 97%